Performance analysis of a prototype solar photovoltaic/wickless heat pipe embedded aluminum curtain wall-heat pump water heating system. (15th April 2022) - Tomar, Vivek; Tsang, Ernest Kin W.; Li, Danny H.W.
Highlights: Introducing the concept and operating principle of a prototype PV-HPCW heat pump water heating system. Introducing the outdoor experimentation of a prototype PV-HPCW module. Introducing a dynamic model to predict the system performance. The dynamic model is validated in outdoor condition with experimental observation of the system. Dynamic thermal and electrical behaviors of PV-HPCW heat pump water heating system are monitor in outdoor condition. Abstract: In this study, a novel glazed photovoltaic heat pipe based curtain wall (PV-HPCW) heat pump system composes of the wickless heat pipe embedded aluminum veneer curtain wall as solar thermal collecting system and heat pump water heating system is proposed. This system assists in heat redistribution on the outer wall of the room to increase solar collection rather than transmission, and in which the collected heat is then transferred to the cold feed of the domestic hot water heating system. A dynamic model is developed to analyze the energy conversion and heat transfer process in the entire system by utilizing the energy balance approach to understand inter-connection and definition of the sorted equations. An experiment is executed and tested under the real outdoor weather conditions in Hong Kong, which is done by measuring the operational parameters, such as solar radiation, PV power generation, temperature at various points and compressor consumption. The simulation results reflect good consistency with the observation data, and indicating that the established model has reasonable accuracy to predict system performance. In outdoor condition, the results indicate that the average electrical and thermal efficiency of PV-HPCW module are around 9.44% and 20.22%, respectively; Similarly, the overall thermal efficiency and overall electrical efficiency (exergy) of the system are 44.6% and 12.8%, respectively; whilst the mean coefficient of performance, COP and the comprehensive coefficient of performance, COPpvt of the system are 3.64 and 5.12 respectively. The PV-HPCW heat pump system has a significant potential and benefits relating to solar heat and electricity. Thus, this innovative PVT technology based building envelop could be a promising building energy supply system with the advantage of proper resource utilization and compact structure, and all these positive implication would encourage the development of such high performance technology, which will contribute to the reduction of carbon emissions in the building sector and ultimately to reduce the urban heat island effect.